Hydraulic Fracturing Stimulation Planning of “X” Well in Talang Akar Formation - Helmy, Mia Ferian; Nugraha, Fanata Yudha; Boni Swadesi; Dewi Asmorowati; Susanti Rina (Penerbitan Universitas Trisakti, 2025)
“X” well is a well with a productive sandstone formation with a productivity index of 0.1 bfpd/psi. Hydraulic fracturing will be performed based on screening results, with design simulated using commercial software. The design process includes analyzing well data, reservoir characteristics, and rock geomechanics using the Perkins, Kern, and Nordgren (PKN) fracture model. The chosen fracturing fluid is YF135.1HTD with Carbolite Proppant (12/18 mesh). The geometric model applied uses the PKN method with results of a fracture length of 463.9 ft, fracture height of 9.84 ft, fracture width of 0.37 inch, and fracture conductivity of 77063 md.ft using a total volume of fracturing fluid of 13500 gallons and a total mass of proppant. amounting to 40590 lbs. The required surface injection pressure is 4176.13 psi with an injection rate of 18 bpm and a total pumping time of 20.2 minutes. The performance improvement of the “X” well was in the form of average formation permeability from 29.2 mD to 369.4 mD, an increase in productivity index of 6.5 times and an increase in production rate from 50.46 bfpd to 296.48 bfpd. So, the planning of the hydraulic fracturing design for the “X” Well can be considered for implementation.